Brief Report: Risk of Adverse Fetal Outcomes Associated With Immunosuppressive Medications for Chronic Immune‐Mediated Diseases in Pregnancy1. Issue 2 (February 2014) - Cooper, William O.; Cheetham, T. Craig; Li, De‐Kun; Stein, C. Michael; Callahan, S. Todd; Morgan, Thomas M.; Shintani, Ayumi K.; Chen, Ning; Griffin, Marie R.; Ray, Wayne A.
<x xml:space="preserve">Abstract</x> Objective To assess the risk of adverse fetal outcomes following exposure to individual immunosuppressive drugs in pregnant women with chronic immune‐mediated diseases. Methods Health plan data were obtained from the Tennessee Medicaid and Kaiser Permanente Northern California and Southern California claims databases, with linkage to both vital records and medical records. Women with inflammatory arthropathies, those with systemic lupus erythematosus, and those with inflammatory bowel disease who filled prescriptions for immunosuppressive treatments during pregnancy were included. Major congenital malformations, fetal deaths, and life‐threatening neonatal complications were identified from the electronic data and validated with medical record review. Results The cohort included 608 infants, including 437 with exposure to immunosuppressive drugs during the mother's pregnancy (402 during the first trimester, and 35 during the second and third trimester only) and 171 whose mothers filled prescriptions for immunosuppressive treatments before, but not during, pregnancy. There were 25 pregnancies (4.1% of the cohort) with confirmed major congenital malformations, and 10 fetal deaths (1.6% of the cohort). Among 113 preterm infants with exposures during pregnancy, 23 (20.4%) had life‐threatening neonatal complications, and among 485 term infants, 10 (2.1%) had life‐threatening complications. Compared to the reference group (treatment before, but not during, pregnancy), the risk ratios (RRs) for adverse fetal outcomes associated with immunosuppressive treatments (by exposure category) during pregnancy included the following: methotrexate (RR 1.39, 95% confidence interval [95% CI] 0.43–4.53), tumor necrosis factor inhibitors (RR 0.98, 95% CI 0.38–2.55), hydroxychloroquine (RR 1.33, 95% CI 0.69–2.55), and other immunosuppressive medications (RR 0.98, 95% CI 0.48–1.98). Conclusion In this study, there was no evidence of a large increase in risk of adverse fetal outcomes from first‐trimester exposure to immunosuppressive medications, although the confidence intervals for the risk ratios were wide. Further studies will be needed as use of these medications increases over time.